Optoretinography reveals comprehensive nanoscopic dynamics of the outer retina in rodents - Tan, Bingyao (2024)
Small animals, such as rodents, are attractive options for investigating the intrinsic process of retinal degeneration. In this study, we used phase-sensitive optical coherence tomography to explore the comprehensive dynamics of rats’ outer retinas in response to visual stimuli. By calculating the temporal phase difference between different outer retinal bands, we revealed highly reproducible retinal dynamics, on the order of tens of nanometers, related to different parts of the outer retina. Our approach may pave the way for preclinical optoretinography study in small animals, facilitating clinical translations for the early detection of neurodegenerative diseases.